Perkuatan Fondasi Telapak Dengan Turap - Sumiyanto, Sumiyanto; Nugroho, Paulus Setyo (Jenderal Soedirman University, 2011)
Reinforcement Foundation is a method to increase the capacity of supporters, so they can support the load of the building. This is required for buildings located on soft ground. Strengtheningthis foundation is also needed if the structure above will be increased so that the burden of building work increased. In this study, attempted to strengthen the foundations of the method by placing the sheet piles on the side of the foundation. Tests performed on two-dimensional model in thelaboratory, by comparing the carrying capacity of thefoundation with sheet piles and without sheet piles. Strengthening the foundation carried outwith3 (three) length variation of plaster that is: L / B = 0.75, L / B = 1.00 and L / B = 1.25. B, and 3 (three) variations in thelocation of plaster, which is in distance S /B = 0.5, S / B = 1.0 andS / B = 1.5. Test results showed that the installation of sheet piles can increase the capacity of foundation support. The results ofthis study showed the longer the higher the sheet piles supporting capacity building, with the results of 33%, 55% and (80% -100%), one each for L/ B = 0.75; 1.00 and 1.25. However, increasedcapacity is not much influenced by the location of plaster especially for short plasterof L / B = 0,75 and L /B = 1,00. While for L/ B =1,25, where the sheet piles getting closeto the foundation, increase capacity increased aswell..